Object Detection in Last Decade - A Survey* - Arshad, Usama (Scientific Journal of Informatics, 2021)
Purpose: In the last decade, object detection is one of the interesting topics that played an important role in revolutionizing the present era. Especially when it comes to computer vision, object detection is a challenging and most fundamental problem. Researchers in the last decade enhanced object detection and made many advanced discoveries using technological advancements. Methods: This research work describes the advancements in object detection over the last 10 years (2010-2020). Different papers published in last 10 years related to object detection and its types are discussed with respect to their role in the advancement of object detection. Result: This research work also describes different types of object detection, which include text detection, face detection etc. It clearly describes the changes in object detection techniques over the period of last 10 years. Object detection is divided into two groups. General detection and Task-based detection. General detection is discussed chronologically and with its different variants while task-based detection includes many state-of-the-art algorithms and techniques according to tasks. This paper also described the basic comparison of how some algorithms and techniques have been updated and played a major role in advancements of different fields related to object detection. Novelty: This research concludes that the most important advancements that happened in last decade and future is promising much more advancement in object detection on the basis of work done in this decade.